Impact of Family-Based Intervention on Quality of Life of Caregivers of Patients with Schizophrenia: A Randomized Controlled Trial in Kerala, India - Sreejamol MG Moonnukandathil; Bindu Menon; Anoop Vincent; Febu E Joy; Praveen Arathil; Arun Kuruppath (National Journal of Community Medicine, 2026)
Background: Caregivers of patients with schizophrenia experience substantial psychosocial burden and impaired Quality-of-life (QoL). Family-Based Interventions (FBIs) may improve caregiver outcomes. The objective was to examine the impact of a Family-Based Intervention on the quality of life of caregivers of patients with schizophrenia. Methods: A two-arm, parallel-group randomized controlled trial was conducted among 84 caregivers recruited from two tertiary care hospitals in Kochi, between October 2024 and March 2025. The experimental group received a Family-Based Intervention, while the control group received routine treatment and care. Caregivers’ quality of life was assessed using the Adult Carer Quality-of-life (AC-QoL) questionnaire at baseline and post-intervention. Data were analyzed using IBM SPSS Statistics version 27.0. Results: Baseline QoL scores were comparable between groups (experimental: 61.3 ± 14.8, control: 63.5 ± 12.2; p = 0.459). Post-intervention, the experimental group demonstrated significantly higher QoL than the control group (87.9 ± 9.7 vs 62.8 ± 11.5; t=10.81, p